2009
DOI: 10.1016/j.seizure.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Retinal ganglion cell toxicity due to oxcarbazepine and valproic acid treatment in rat

Abstract: OXC seems to be toxic to RGCs at 100mg/kg dose when it is been given as a monotherapy or combined with VPA. Single VPA treatment has no effect on RGC number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…This observation of mild cell toxicity induced by OX is in agreement with previous finding [40,82] that showed OX as an agent that can cause anatomic and organizational disruption in cell layers, nuclear shrinkage, and cell atrophy. Conclusively, these findings would add to our previous finding that emulsomes can shield OX cell damaging effects [40] the ability of G16 emulsomal thermogel composite to further protect nasal cells from the severe effect of OX.…”
Section: Resultssupporting
confidence: 93%
“…This observation of mild cell toxicity induced by OX is in agreement with previous finding [40,82] that showed OX as an agent that can cause anatomic and organizational disruption in cell layers, nuclear shrinkage, and cell atrophy. Conclusively, these findings would add to our previous finding that emulsomes can shield OX cell damaging effects [40] the ability of G16 emulsomal thermogel composite to further protect nasal cells from the severe effect of OX.…”
Section: Resultssupporting
confidence: 93%
“…However, no significant differences were found between groups. 10,41 Aktas et al 42 studied the histopathologic changes in vivo in retina ganglion cell layer induced by VPA and OXC and found that VPA causes RGC atrophy without significant RGC loss whereas OXC treatment led significant negative effects on the structure and number of the RGCs and concluded that the color vision deficits due to VPA may be related with ganglion cell loss; the study was an in vivo study and degree of the toxicity was associated with the duration of the treatment and the dose of the antiepileptic drug, and the doses applied in vivo were not directly related to the doses used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…53 In accordance with our results, VPA treatment per se had no effect on RGC number even after 90 days of VPA treatment. 54 If VPA will be considered in future for the treatment of a chronic retinal neurodegenerative disease such as glaucoma, possible effects of VPA on retinal function have to be monitored carefully.…”
Section: Discussionmentioning
confidence: 99%